Regalos, viajes y gastos de hospitalidad. Corrupción penal en la esfera de los negocios - Carnevali Rodríguez, Raúl A. (2024)
There is a growing concern for having better tools to address corruption, so much so that since the 1990s various international instruments have been issued, urging States to strengthen their legislation. Although this phenomenon has traditionally been associated with the public sphere, the need to criminalize corrupt acts that take place in the private sphere is no longer questioned. Proof of this is the growing criminalization of corruption between private individuals. In this regard, one of the traditional expenses incurred by private companies is related to hospitality, such as gifts and travel aimed at promoting products or for the training of their employees and customers. However, the line that separates these expenses from improper practices that affect fair competition can be quite blurred since they could be used for bribery. Given the above, it is essential to have guiding criteria that allow one to act with clarity to prevent corrupt conduct. To this end, this paper examines the Foreign Corrupt Practices Act and the Bribery Act, since their regulations, as well as the recommendations issued by public agencies, both in the United States and the United Kingdom, provide important guiding principles that allow private companies to specify their compliance programs to have measures and procedures in place to prevent their hospitality expenses from being classified as corrupt.